L’harmonie vocalique en joola fooñi - Bassène, Alain Christian (AAeO - Afrikanistik-Aegyptologie-Online, 2018)
In the languages which compose the Joola linguistic group, as in some languages of the Atlantic group, there is a distribution of vowels into two different series : +ATR vowels and –ATR vowels. All the works on these languages describe a system with a vowel harmony phenomenon according to which the two series of vowels do not combine with one another, inside the word, that is to say that inside of a word, all the vowels are either +ATR or –ATR. In joola fooñi, this is not always systematic. We shall see, in this article, that the absence of total vowel harmony in joola fooñi, is partly due to the degree of variable integration of bound morphemes.